The Effect of Financial Literacy on Financial Behavior of Micro, Small and Medium Enterprises (SMEs) in Ulugawo District, Nias Regency - Zai, Sambuani; Hulu, Perlindungan F.; Bate’e, Maria Magdalena; Bu’ulolo, Nanny A. (Golden Ratio of Data in Summary, 2024)
Low financial literacy has significant implications, including restricted access to financial institutions and mismanagement of money and wealth. A common consequence of low financial literacy is the limited access to financial services, often restricted to banks. This issue is particularly prevalent among Micro, Small, and Medium Enterprises (MSMEs), where poor financial literacy hinders both business growth and economic development. Many individuals lack the financial knowledge necessary to manage investments, pay bills on time, and maintain a budget, all of which are essential for sound financial management. In the case of MSME actors in Ulugawo sub-district, observations reveal that many do not have a clear understanding of financial management, nor do they maintain proper financial records. This lack of financial knowledge often leads to difficulties in organizing expenditures and managing finances. As a result, many MSMEs struggle to present their financial standing clearly, making them ineligible for capital credit access. The purpose of this study was to examine the impact of financial literacy on the financial behavior of MSME actors in Ulugawo, Nias. The research employed a quantitative descriptive approach, with data collected through questionnaires. The data analysis revealed that financial literacy accounts for 70% of the variation in financial behavior among MSMEs in Ulugawo, indicating that the remaining 30% is influenced by other factors not covered in this study. The t-test results for the financial literacy variable (X) showed a t-value of 2.191, with a significance level of 5%. The calculated r-value was greater than the critical r-value (r-calculated > r-estimated, 1.6759), confirming the significant influence of financial literacy on financial behavior.